2011
DOI: 10.4061/2011/376243
|View full text |Cite
|
Sign up to set email alerts
|

Alterations along the Hypothalamic-Pituitary-Thyroid Axis of the Zebrafish (Danio rerio) after Exposure to Propylthiouracil

Abstract: In the past, various approaches have been developed to detect adverse effects of pollutants on the thyroid of vertebrates, most of these with special emphasis on the South African clawed frog, Xenopus laevis. Although fish are primarily affected by thyroid-disrupting chemicals, studies into alterations of the thyroid of fish are scarce. Therefore, effects of the reference compound propylthiouracil on histopathology of the thyroid axis were analyzed in a modified early life-stage test with zebrafish (Danio reri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 109 publications
7
60
2
Order By: Relevance
“…The methods for whole body thyroid hormone extraction and measurement were adopted from previous methods (Schmidt and Braunbeck, 2011;Shi et al, 2009) in zebrafish. 60 larvae were homogenized in 0.5 mL ice-cold methanol with 1 mM PTU.…”
Section: Thyroid Hormone Extraction and Measurementmentioning
confidence: 99%
“…The methods for whole body thyroid hormone extraction and measurement were adopted from previous methods (Schmidt and Braunbeck, 2011;Shi et al, 2009) in zebrafish. 60 larvae were homogenized in 0.5 mL ice-cold methanol with 1 mM PTU.…”
Section: Thyroid Hormone Extraction and Measurementmentioning
confidence: 99%
“…Several studies have demonstrated the sensitivity of the HPT axis in Xenopus laevis to a variety of known thyroid disrupting chemicals, including perchlorate, 6-propylthiouracil, methimazole, and ethylenethiourea Tietge et al, 2005Tietge et al, , 2010Opitz et al, 2009). Zebrafish thyroid system is similar to the mammalian or the amphibian thyroid system, and zebrafish has become very popular vertebrate model to screen for thyroid-disrupting chemical pollutants, and evaluating their risk to animals and humans (Raldua and Babin, 2009;Schmidt and Braunbeck, 2011;Heijlen et al, 2013). Recently, an in vivo model for testing endocrine disruption of THs was developed using zebrafish larvae (Yu et al, 2010;Schmidt and Braunbeck, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish thyroid system is similar to the mammalian or the amphibian thyroid system, and zebrafish has become very popular vertebrate model to screen for thyroid-disrupting chemical pollutants, and evaluating their risk to animals and humans (Raldua and Babin, 2009;Schmidt and Braunbeck, 2011;Heijlen et al, 2013). Recently, an in vivo model for testing endocrine disruption of THs was developed using zebrafish larvae (Yu et al, 2010;Schmidt and Braunbeck, 2011). This assay indicated that the zebrafish HPT axis can be used to determine thyroid endocrine system disruption by TH endocrine disruptors, and also, to some extent, to indicate potential mechanisms of action, e.g., polybrominated diphenyl ethers (PBDEs) (Yu et al, 2010;Chan and Chan, 2012), herbicide ioxynil (Campinho and Power, 2013), fungicides hexaconazole and tebuconazole (Yu et al, 2013), and triclosan (Pinto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Treatment concentrations of PTU have been reported to result in depigmentation and clear effects on the thyroid at levels above 50 mg/L (Schmidt and Braunbeck, 2011;Van der Ven et al, 2006b). TBBPA was dissolved in DMSO with a maximal final concentration in the exposure medium of 0.04%.…”
Section: Test Chemicalsmentioning
confidence: 99%
“…Consequently, the chemical often serves as reference substance in exposure experiments on the thyroid system. Recent studies revealed the adverse effect of PTU on the zebrafish thyroid system (Schmidt and Braunbeck, 2011) and embryonic development (Jomaa, 2014). Also effects of PTU on fish eye development have been reported (Macaulay et al, 2015;Raine and Hawryshyn, 2009), which makes it an interesting candidate for the current project.…”
Section: Introductionmentioning
confidence: 99%